Growth of copper nanocubes on graphene paper as free-standing electrodes for direct hydrazine fuel cells - Gao, Hongcai (2013)
We have developed a new type of flexible electrodes based on Cu nanocube-decorated free-standing graphene paper (GP) using a facile electrodeposition method. The Cu nanocubes–graphene paper (Cu–GP) hybrid electrode processes remarkable electrocatalytic activity with an onset potential of −0.10 V toward hydrazine oxidation in alkaline solutions and can serve as the catalyst layer for direct hydrazine fuel cells. One interesting finding is that a copper hydroxide/oxide layer in situ formed on Cu nanocube surfaces plays an important role in enhancing the electrocatalytic activity and durability of the electrocatalyst. A totally irreversible and diffusion-controlled oxidation of hydrazine occurs on the electrocatalyst, eventually leading to environmentally friendly products such as nitrogen and water.